2017
DOI: 10.1515/jolace-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Foreign-language teaching and studying in Chilean and Finnish classrooms as seen by teachers

Abstract: This article reports Chilean and Finnish foreign-language (FL) teachers' perceptions of teaching and study realities in their own FL classrooms. Communicative language teaching (CLT) is used as the teaching-studying-learning methodological framework of an international KIELO project (= the acronym for Finnish "kieltenopetus" meaning "language teaching"), whose online survey was used to collect data for this article. We aim at answering the following research question: What are the FL teachers' main approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The existing body of research has indicated that textbooks guide the pedagogical content and teaching methods employed by educators during lessons, albeit with some variation in the scope and degree of this influence among educators (Brown, 2009;Harjanne et al, 2017;Karvonen et al, 2018). In addition, textbooks themselves have an inherent value as a pedagogical tool: they can be used as self-study materials and as materials for homeschooling.…”
Section: Promoting Sustainable Behavior Through Textbooksmentioning
confidence: 99%
“…The existing body of research has indicated that textbooks guide the pedagogical content and teaching methods employed by educators during lessons, albeit with some variation in the scope and degree of this influence among educators (Brown, 2009;Harjanne et al, 2017;Karvonen et al, 2018). In addition, textbooks themselves have an inherent value as a pedagogical tool: they can be used as self-study materials and as materials for homeschooling.…”
Section: Promoting Sustainable Behavior Through Textbooksmentioning
confidence: 99%
“…Starting to use action-based tasks in language learning might be a substantial change from normal practices for subject teachers. Teaching foreign languages in Finland is often book-based with limited communicative activities (Harjanne et al, 2017).…”
Section: Ability To Throw Oneself In the Jobmentioning
confidence: 99%
“…Research studying basic and upper secondary education shows that language teachers use textbooks to a great extent (Harjanne et al, 2015), and that language teachers can be divided into two groups: those who favour communicative tasks and those who favour non-communicative tasks (Harjanne et al, 2015;Harjanne et al, 2017). In terms of challenges, language teachers rely on the mother tongue extensively, and meaningful communicative tasks are not frequently employed (Harjanne et al, 2017). In addition, the Finnish Education Evaluation Centre (FINEEC) has assessed students' language proficiency in several languages.…”
Section: Introductionmentioning
confidence: 99%